Lower extremity exercise of knee osteoarthritis patients using portable assistive robot (HEXAR-KR40P) - Kim, Mi Jung; Lee, Dong Hun; Kim, Taikon; Jang, Seongho; Kim, Hee-Sang; Chon, Jinmann; Yoo, Seung Don; Ahn, Jae Yong; Han, Jungsoo; Jang, Hye-Youn; Yun, Deok-Won; Han, Changsoo (International journal of precision engineering and manufacturing, 2014)
We studied newly developed assistive robot movement (ARM, HEXAR-KR40P) equipment, and compared with conventional continuous passive movement (CPM) equipment, focusing on range of motion (ROM) and strengthening of knee joint muscles. 110 osteoarthritis (OA) patients were recruited from five different clinics. At first, eighty patients were enrolled to evaluate the subjective satisfaction of ARM. Secondly, thirty patients were enrolled to find the effectiveness of ARM including ROM and strength compared with CPM. Subjects in first study performed exercise for two weeks. Exercise was performed with CPM and ARM for ten minutes alternately. Subjects in second study performed exercise with ARM only 30 min/day for two weeks, and measured ROM, strength, and functional changes. Obtained data was analyzed with Wilcoxon signed rank test. As a result, higher subjective satisfaction with ARM in patients and researchers survey was noted compared with CPM (p<0.05). Active and passive ROMs of knee flexion were significantly improved after ARM exercise. Strength of knee muscles, timed up and go test (TUGT), sit-and-stand-up of short physical performance battery (SPPB) score were also significantly improved after ARM exercise. Findings suggest that ARM equipment performed better than CPM equipment for knee OA patients to increase in ROM and strength.